Social Conformity, Deviation, and Opportunity Structures: A Comment on the Contributions of Dubin and Cloward - Merton, Robert K. (American Sociological Review, 1959)
Six of the articles in this issue of the Review are concerned with deviant behavior. And three articles-those by Robert Dubin and Richard A. Cloward, upon which Professor Merton comments, and the following paper by Dorothy L. Meier and Wendell Bell-are clearly in the Durkheimian tradition. It is not surprising that these contributions conspicuously exploit Merton's essay, Social Structure and Anomie, first published in 1938, itself a modern landmark in that tradition. These papers not only illustrate the continuing influence of Durkheim but they specify possibilities, at least, of cumulative theoretical development. Professor Merton's commentary-written at short notice, and at the request of a persistent but grateful editor-attests once more to the viability of the tradition and promises further significant analysis of deviant behavior, to be sure, and of conformity conduct as well. -The Editor.